Prevalencia de gingivitis asociada a placa bacteriana en los pacientes de 25 a 50 años que acuden a la consulta odontológica del Hospital Básico 7 B. I Loja, periodo noviembre 2017 - marzo 2018 - Guerrero Lima, Thalya Valentina (2018)
Gingival disease is a public health problem with high prevalence worldwide. The objective of this research was to determine the prevalence of gingivitis associated with bacterial plaque in patients from the ages of 25 to 50 years who attend the dental clinic of Basic Hospital 7 BI Loja, period November 2017 - March 2018. The research design of this study was of a descriptive and cross-sectional type, it had a sample of 96 study units, and an observation sheet was prepared to obtain the data. The index used to determine the degree of gingival disease was the gingival index of Löe and Silness, for which the OMS periodontal probe was used. Once the data were obtained, the index of each participant was analyzed, where it was found that the prevalence of gingival disease in the sample was 83%, showing a higher percentage in moderate grades. While, the degree of oral hygiene of the patients was determined by the simplified oral hygiene index (IHOS), the highest prevalence being in an acceptable hygiene on the part of the young adult. It was concluded that there is a prevalence of gingivitis associated with bacterial plaque in patients who come to the dental clinic of the Basic Hospital 7 B.I Loja. Key words: Gingival disease, Bacterial plaque, Gingival index, IHOS.